Coordinated regulation of octopine degradation and conjugative transfer of Ti plasmids in Agrobacterium tumefaciens: evidence for a common regulatory gene and separate operons. - Klapwijk, P M (1978)
By using the analog noroctopine, mutants of agrobacterium tumefaciens were isolated with altered regulation patterns for the Ti plasmid-borne octopine utilization genes. These could be divided into three classes: (i) strains with a constitutive level of octopine enzymes and a high degree of spontaneous Ti transfer; (ii) one strain with constitutive octopine enzymes but no spontaneous Ti transfer; and (iii) strains with an altered inducibility in which, contrary to the wild-type Ti plasmid, conjugation and octopine utilization were induced by noroctopine. These results are best explained by the activity of a common regulatory gene. In a second step, using homo-octopine, mutants were isolated with lesions preventing the utilization of octopine. All mutations were plasmid borne and did not prevent the induction of tumors. Plasmids of two isolates were characterized by large deletions resulting in a decreased virulence and the absence of octopine in the tumor. With a plasmid carrying an inserted transposon Tn1, a significant number of strains were isolated which were unable both utilize octopine and to transfer the Ti plasmid. This suggests that there may be another common factor--presumably positive--between these traits. Transfer-negative mutants were still virulent. This seems to exclude a role for the conjugative transfer during the process of plant tumor induction. A way to test octopine oxidase by the use of permeable cells is described.